Medicinal Plant Images - Cock, I.E. (Pharmacognosy Communications)
Tasmannia lanceolata (commonly known as Tasmanian pepper or mountain pepper) is a medium to large shrub (2-5 m in height) which is endemic to the woodlands and cool temperate rainforests of Tasmania and the south-eastern region of the Australian mainland.1 Individual plants are unisexual, having either male or female flowers. The berries, leaves and bark of this species have historical uses as a food and as a medicinal plant.2 When the berry is air dried it forms a small, hard peppercorn which is suitable for milling or crushing. The berry has a pleasant spicy flavour and sharp aroma. T. lanceolata was used as flavouring agent by Australian Aborigines and more recently by European settlers. Historically, the leaves have been used as a herb and the berries have been used as a spice. Australian Aborigines also used T. lanceolata as a therapeutic agent to treat stomach disorders and as an emetic, as well as general usage as a tonic.2 Reports also exist of the use of T. lanceolata by Australian Aborigines for the treatment and cure of skin disorders, venereal diseases, colic, stomach ache and as a quinine substitute.2 Later, European colonists also recognized the therapeutic potential of T. lanceolata and the bark was used as a common substitute for other herbal remedies (including those derived from the related South American Winteraceae species, Drimys wintera (winter bark)3 to treat scurvy due to its high antioxidant content.2,4 Recent studies have reported T. lanceolata extracts to be potent inhibitor of the growth of an extensive panel of bacteria,5 and of a bacterial trigger of rheumatoid arthritis.6 T. lanceolata extracts have also been reported to inhibit the proliferation of the gastrointestinal protozoal parasite Giardia duodenalis.7 This photograph was taken in Tasmania, Australia in 2014 by Dr David Ruebhart and is printed here with the photographer’s permission.